Visual transduction in Drosophila. - Hardie, R.C.; Raghu, P. (Nature, 2001)
The brain's capacity to analyse and interpret information is limited ultimately by the input it receives. This sets a premium on information capacity of sensory receptors, which can be maximized by optimizing sensitivity, speed and reliability of response. Nowhere is selection pressure for information capacity stronger than in the visual system, where speed and sensitivity can mean the difference between life and death. Phototransduction in flies represents the fastest G-protein-signalling cascade known. Analysis in Drosophila has revealed many of the underlying molecular strategies, leading to the discovery and characterization of signalling molecules of widespread importance.